2005
DOI: 10.1097/01.gim.0000182466.87113.ce
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genotypic and phenotypic strategies for population screening in hemochromatosis: Assessment of anxiety, depression, and perception of health

Abstract: Purpose: Hemochromatosis is a treatable disorder with a major genetic predisposition. It provides an example in which genotypic and phenotypic strategies for screening may be compared. We previously showed noninferiority of uptake of a genotypic population screening strategy for hemochromatosis compared with a phenotypic strategy. In this article we present the psychologic effects of each strategy. Methods: A sample of 3000 individuals from primary care were randomly allocated to a phenotypic or genotypic scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…A recent meta-analysis [78] reviewed only 3 small cohorts and, although the evidence was limited, concluded that there is no demonstrable rise in anxiety levels or decrease in quality-of-life scores following testing. This concurs with population screening studies, which have found both genotypic and phenotypic methods to be acceptable and producing no evidence of psychological disturbance [79,80].…”
Section: Diagnosis and Screeningsupporting
confidence: 86%
“…A recent meta-analysis [78] reviewed only 3 small cohorts and, although the evidence was limited, concluded that there is no demonstrable rise in anxiety levels or decrease in quality-of-life scores following testing. This concurs with population screening studies, which have found both genotypic and phenotypic methods to be acceptable and producing no evidence of psychological disturbance [79,80].…”
Section: Diagnosis and Screeningsupporting
confidence: 86%
“…5,10 Other programs have also screened for C282Y/ H63D 11 or H63D/H63D. 12 Some have decided not to inform heterozygotes about their status 13 or instead to tell ϩ/ϩ individuals and C282Y carriers just that they were at "low risk to develop hemochromatosis" while inviting them to call if they wished to learn their actual genotype. 5 Giving genotype information only to those at higher risk of IO is a strategy that may lessen confusion among low-risk carriers, but it reduces the chance to identify relatives with higherrisk genotypes through cascade screening.…”
Section: Io Statusmentioning
confidence: 99%
“…However, population screening studies that were excluded from this review (Bryant et al, 2009) and others report similar findings to those reported here. For instance, when phenotypic and genotypic screening strategies have been compared, both have been acceptable (Anderson et al, 2005;Patch et al, 2005b) and little psychological disturbance has been apparent in the short term with either strategy (Patch et al, 2004;Patch et al, 2005a). Negative psychosocial consequences have been reported to be rare (Power et al, 2007;Stuhrmann et al, 2005) and in common with the results reported in this review; receipt of indeterminate test results for hemochromatosis is associated with mild negative effects (Anderson et al, 2006).…”
mentioning
confidence: 57%